Magma Vesiculation and Nature of the Explosive Activity in the 2011 Grímsvötn Eruption - Lynch, Rebecca A., 1990- (2015)
Grímsvötn is a basaltic, subglacial volcano and is the most active volcano in Iceland. It is known for phreatomagmatism and historically large fissure eruptions from its associated fissure swarm. The Grímsvötn central volcano erupted in 2004 from vents in the SW corner of the caldera, and again in 2011 from the same vent with more explosive intensity, magma volume and up to 19km-high eruption plume, suggesting an event of Plinian intensity. The deposits of the 2011 eruption consists of six alternating pumice lapilli and ash-grade units that raise questions about the potential role of magma outgassing in driving fragmentation and about the explosive nature of the 2011 eruption. To assess the degassing and fragmentation characteristics of this eruption, density measurements of 1200 clasts, from 12 samples spread across the three pumice lapilli units and quantitative image analysis were performed for four selected clasts from the lapilli units. The mean vesicularities are uniform, between 78.8% and 87.8%, indicating a degassed and fully expanded magma column upon magma disintegration. This high level of vesicularity resulted in convoluted bubble textures. Bubble-to-bubble interaction resulted in significant bubble coalescence, thin vesicle walls and collapse, as well as the formation of possible tube-like degassing pathways. The highly expanded and effective degassed magma column indicates volatile driven disintegration of the magma upon eruption. However, the alternating lapilli pumice and ash-grade units can be explained by (i) changes in eruption intensity or (ii) two stages of fragmentation, where an initial fragmentation to predominantly lapilli-size pumices is driven by expansion of magmatic gases (i.e. dry eruption) and a second-stage fragmentation induced by (a) passive (quenched fragmentation) or (b) explosive (fuel-coolant-like) interaction of magma and external water. Grímsvötn er basalt megineldstöð undir Vatnajökli og tilheyrir samnefndu eldstöðvakerfi. Hún er ein virkasta eldstöð landsins og þekkt ...